Conjugated polymer donor–molecular acceptor nanohybrids for photocatalytic hydrogen evolution. Issue 50 (19th May 2020) - Yang, Haofan; Li, Xiaobo; Sprick, Reiner Sebastian; Cooper, Andrew I.
Abstract : Learning from OPV: Highly efficient nanohybrid photocatalysts that combine conjugated polymer donors with molecular acceptors was discovered for photocatalytic sacrificial hydrogen evolution reaction. Abstract : A library of 237 organic binary/ternary nanohybrids consisting of conjugated polymers donors and either fullerene or non-fullerene molecular acceptors was prepared and screened for sacrificial photocatalytic hydrogen evolution activity. PCDTBT/PC60 BM nanohybrid showed a high hydrogen evolution rate of 105.2 mmol g −1 h −1 under visible light ( λ > 420 nm).